Regulated phosphorylation of the K-Cl cotransporter KCC3 is a molecular switch of intracellular potassium content and cell volume homeostasis - Adragna, Norma C.; Ravilla, Nagendra B.; Lauf, Peter K.; Begum, Gulnaz; Khanna, Arjun R.; Sun, Dandan; Kahle, Kristopher T. (Frontiers in Cellular Neuroscience, 2015)
The defense of cell volume against excessive shrinkage or swelling is a requirement for cell function and organismal survival. Cell swelling triggers a coordinated homeostatic response termed regulatory volume decrease (RVD), resulting in K+ and Cl– efflux via the activation of K+ channels, volume-regulated anion channels (VRACs), and the K+-Cl– cotransporters, including KCC3. Here, we show genetic alanine (Ala) substitution at threonines (Thr) 991 and 1048 in the KCC3a isoform carboxyl-terminus, preventing inhibitory phosphorylation at these sites, not only significantly up-regulates KCC3a activity up to 25-fold in normally inhibitory isotonic conditions, but is also accompanied by reversal of activity of the related bumetanide-sensitive Na+-K+-2Cl– cotransporter isoform 1 (NKCC1). This results in a rapid (<10 min) and significant (>90 %) reduction in intracellular K+ content (Ki) via both Cl-dependent (KCC3a + NKCC1) and Cl-independent (DCPIB [VRAC inhibitor]-sensitive) pathways, which collectively renders cells less prone to acute swelling in hypotonic osmotic stress. Together, these data demonstrate the phosphorylation state of Thr991/Thr1048 in the KCC3a encodes a potent switch of transporter activity, Ki homeostasis, and cell volume regulation, and reveal novel observations into the functional interaction among ion transport molecules involved in RVD.